AN ANALYSIS OF ENGLISH SPEECH STYLE AS REFLECTED BY THE MAIN CHARACTER OF A TALE OF TWO CITIES - Mohammad Amiruddin; Matlub Matlub (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2017)
This research aims at finding out the kinds of English speech style as reflected by Sydney Carton, the main character, of A Tale of Two Cities, the functions of the speech styles, and the influences of social environment on English speech style as reflected by Sydney Carton in A Tale of Two Cities. The research is descriptive-qualitative. The data were in the form of utterances: words, phrases, clauses, and sentences uttered by Sydney Carton in A Tale of Two Cities. The main instrument of the research was the researcher himself. The researcher also triangulated the data to achieve trustworthiness by doing consultations and checking to friends. The result of the analysis shows that there are four kinds of English speech style reflected by the main character of A Tale of Two Cities. They are formal, consultative, casual, and intimate styles. The highest percentage of the kinds of English speech style in A Tale of Two Cities belongs to intimate style (44 %), when Sydney Carton talks to a woman he loves, Miss Manette. The lowest percentage of English speech style belongs to consultative style (8 %), when Sydney Carton is in a small discussion about the secret interview and the ways to save Charles Darnay. In the novel, there are two functions of English speech style: giving information about social status and mood. The function of English speech style reflected by Sydney Carton with the highest percentage is giving information about mood (92 %), especially when Sydney Carton wants to show Miss Manette that he needs her in his life (16 %). The lowest percentage is giving information about social status (8 %), when Sydney Carton asks the officer to help Miss Manette and when he wants to show Mr.Lorry that Sydney Carton know Miss Manette well. Giving information about mood is much more often used than social status because the situation in that time are unrest and full of violence. Besides, the story is about a romantic relationship between Carton and the woman he loves. There are three influences of social environment on English speech style. They are the choice of words, grammatical construction, and voice quality. The influence of social environment on speech style reflected by Sydney Carton with the highest percentage is choice of words (46 %), especially when there is no delicacy of the fellow in conversation with Miss Manette (36 %). The next percentage belongs to voice quality (32 %), shown through his conversation with Mrs Manette. The lowest percentage belongs to grammatical construction (4 %), when no one gives acknowledgment to Sydney Carton.